Partial nephrectomy: is there an advantage of the self-retaining barbed suture in the perioperative period? - Zondervan, Patricia J.; Gözen, Ali Serdar; Rassweiler, Jens (World journal of urology, 2012)
OBJECTIVE: To evaluate the efficacy of the self-retaining barbed suture (SRBS) in renal defect repair during partial nephrectomy (PN), by assessing perioperative outcomes. METHODS: From June 2010 on we have been using the SRBS for superficial layer closure during open and laparoscopic PN in two European centers. These data were collected prospectively and matched with historical PN cases performed with conventional suture. Cases were matched for PADUA score, surgical approach (laparoscopic or open) and the center where surgery was performed. Comparisons were made in patient characteristics and perioperative outcomes including warm ischemia time (WIT), changes in hemoglobin (Hb), changes in estimated glomerular filtration rate (eGFR) and perioperative complications between the SRBS and non-SRBS groups. Statistical tests of significance were performed using Student's t test and chi-square test for continuous and categorical variables, respectively. RESULTS: Thirty-one consecutive cases of PN under WIT were performed with SRBS. These cases were matched with cases from the historical database of PN performed with conventional suture. The rate of perioperative complications was statistically significantly lower in the SRBS cohort (6.5 vs. 22.6 %, p = 0.038). Mean ischemia time was 19.6 min (SD, 7.5) in the SRBS group versus 21.8 min (SD, 9.5) in the conventional suture group (p = 0.312). There were no significant differences between groups for postoperative changes in creatinine, eGFR and Hb. Limitations of this study include the absence of randomization and the relative small sample size. CONCLUSIONS: SRBS can be safely used during partial nephrectomy. SRBS reduces significantly the number of perioperative complications.